Pelatihan Pembuatan Product Digital Berbasis WEB untuk Guru Gugus 4 Kota Cirebon - Guntur, Mochamad; Sahronih, Siti; Haryanti, Yuyun Dwi; Fitryarany, Della; Munifah, Afra (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology has brought significant changes to the world of education, particularly in the use of flexible and interactive website-based learning media. However, many teachers still face obstacles in mastering digital skills, thus requiring systematic training. This community service activity aims to improve teachers' competence in utilizing website-based learning platforms, particularly course.akademimerdeka.com, through a series of face-to-face training sessions. The training was conducted in four sessions, namely platform introduction, instructor account creation, digital product development with Canva, and uploading digital products to the platform. There were 12 teachers from Cluster 4, Harjamukti District, Cirebon City, who participated in the activity. The results of the activity showed a significant increase in teachers' motivation to design interesting learning activities (96%), their ability to create game-based activities (92%), students' learning skills (91%), and teachers' involvement in continuing education (95%). Additionally, teachers were able to produce digital products such as e-modules, PowerPoint presentations, posters, and animated videos that are integrated with the learning platform. These findings confirm that technology-based training can strengthen the role of teachers as facilitators and innovators of digital learning. In conclusion, training in the use of website-based platforms is effective in improving teacher competence while encouraging interactive, creative, and flexible learning. Follow-up activities include periodic ongoing training, technical assistance, and expansion of implementation to more schools to optimize the use of technology in the teaching and learning process.